The Dynamics of the Thai-So Ways of Life in Kusuman District, Sakon Nakhon Province - and Sekson Yongvanit, Benjapa Kaithong (Journal of Community Development Research (Humanities and Social Sciences), 2016)
The aim of this article is to study the changing ways of life of the Thai-So ethnic group from 1844 up to 2014. The purposive sampling technique was used for selecting 42 key informants. The research instruments were semi-structured interviews. The whole data were analyzed by content analysis technique. The findings pointed out that the Thai-So ways of life could be divided into five periods. Each period was based on real events generating turning points in the Thai-So ways of life in Kusuman district. That is to say, there was no evidence indicating the changing ways of life of the Thai-So people in the formative period of Kusuman district (1844-1939). Nevertheless, their ways of life began to change during the war period (1940-1960) and changed more and more during the 1 st -4 th national development period (1961-1983). It was also found that their ways of life were brought into the new economy, society and culture in the transformation period (1984-1993). Namely, they turned themselves into a market-oriented mode of production, sought non-agricultural employment and migrated to work at the industrial Estate Authority and oversea. Finally, their animistic beliefs were regarded as their strongest point, but those beliefs were gradually replaced by the logic belief of Buddhism during the period of opinion leader and informative society (1994-2014). Further analysis revealed that those driving forces – such as the growth of infrastructure, transportation facilities, the development of a large scale market, agriculture innovation, modern medicine, the arrivals of cash crop, the phenomenon of labor migration, and mass media were regarded as the cause of the changing ways of life in 3 dimensions: economic, social and cultural aspects.   Keywords:   Thai-So Ethnic Group, Ways of Life, Kusuman District
Keywords: Thai-So Ethnic Group, Ways of Life, Kusuman District